Head and Neck Kaposi Sarcoma: Clinicopathological Analysis of 11 Cases - Agaimy, Abbas; Müller, Sarina Katrin; Harrer, Thomas; Bauer, Sebastian; Thompson, Lester D. R. (Head and Neck Pathology, 2018)
Kaposi sarcoma (KS) of the head and neck area is uncommon with limited published case series. Our routine and consultation files were reviewed for histologically and immunohistochemically proven KS affecting any cutaneous or mucosal head and neck site. Ten males and one female aged 42-78 years (median, 51 years; mean, 52 years) were retrieved. Eight patients were HIV-positive and three were HIV-negative. The affected sites were skin (n = 5), oral/oropharyngeal mucosa (n = 5), and lymph nodes (n = 3) in variable combination. The ear (pinna and external auditory canal) was affected in two cases; both were HIV-negative. Multifocal non-head and neck KS was reported in 50% of patients. At last follow-up (12-94 months; median, 46 months), most of patients were either KS-free (n = 8) or had ongoing remission under systemic maintenance therapy (n = 2). One patient was alive with KS (poor compliance). Histopathological evaluation showed classical features of KS. One case was predominantly sarcomatoid with prominent inflammation mimicking undifferentiated sarcoma. Immunohistochemistry showed consistent expression of CD31, CD34, ERG, D2-40 and HHV8 in all cases. This is one of the few series devoted to head and neck KS showing high prevalence of HIV-positivity, but also unusual presentations in HIV-negative patients with primary origin in the skin of the ear and the auditory canal. KS should be included in the differential diagnosis of difficult-to-classify spindle cell lesions at this uncommon location.
EVALuna2:207378